2006
DOI: 10.1016/j.ydbio.2006.05.010
|View full text |Cite
|
Sign up to set email alerts
|

FGF2 plays a key role in embryonic cerebrospinal fluid trophic properties over chick embryo neuroepithelial stem cells

Abstract: During early stages of brain development, neuroepithelial stem cells undergo intense proliferation as neurogenesis begins. Fibroblast growth factor 2 (FGF2) has been involved in the regulation of these processes, and although it has been suggested that they work in an autocrine-paracrine mode, there is no general agreement on this because the behavior of neuroepithelial cells is not self-sufficient in explants cultured in vitro. In this work, we show that during early stages of development in chick embryos the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(105 citation statements)
references
References 68 publications
3
97
1
4
Order By: Relevance
“…Specifically, intraventricular injections of FGF2 in embryonic rats and mice increases neocortical neuron numbers (13,29), as one would expect if FGF2 prolongs precursor proliferation. Several studies suggest that proliferation rate and neuronal migration are relatively unaffected by FGF2 manipulations in vivo (13,(29)(30)(31), although in vitro studies have reported more complex effects (32).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, intraventricular injections of FGF2 in embryonic rats and mice increases neocortical neuron numbers (13,29), as one would expect if FGF2 prolongs precursor proliferation. Several studies suggest that proliferation rate and neuronal migration are relatively unaffected by FGF2 manipulations in vivo (13,(29)(30)(31), although in vitro studies have reported more complex effects (32).…”
Section: Resultsmentioning
confidence: 99%
“…Decreasing hydrostatic pressure results in smaller brain ventricles, and smaller and disorganized neural tissue [63]. Factors within the embryonic CSF, including sonic hedgehog and choroid plexus-derived insulin-like growth factor 2, promote the proliferation of neural progenitors [59,78,90,170]. The CSF effect is optimal when age-matched CSF and tissue are combined, highlighting the dynamic nature of both the choroid plexus/CSF axis and of the intrinsic state of the responding cells [18,78].…”
Section: Embryonic and Postnatal Developmentmentioning
confidence: 99%
“…Gato et al and Martin et al have studied the role of chick e-CSF in regulating survival, proliferation, and neurogenesis of neuroepithelial cells, and identified FGF-2 in the chick CSF as a vital trophic factor. 15,16 Intriguingly, in mutant animals, CSF factors that may inhibit proliferation have been suggested. In studies of the hydrocephalic Texas (H-Tx) rat, it has been found that cell proliferation in the ventricular zone decreases, and although cell migration still occurs, there is a decrease in the number of migrating cells.…”
Section: Introductionmentioning
confidence: 99%